2005
DOI: 10.1021/bi051257i
|View full text |Cite
|
Sign up to set email alerts
|

NifS-Mediated Assembly of [4Fe−4S] Clusters in the N- and C-Terminal Domains of the NifU Scaffold Protein

Abstract: NifU is a homodimeric modular protein comprising N- and C-terminal domains and a central domain with a redox-active [2Fe-2S](2+,+) cluster. It plays a crucial role as a scaffold protein for the assembly of the Fe-S clusters required for the maturation of nif-specific Fe-S proteins. In this work, the time course and products of in vitro NifS-mediated iron-sulfur cluster assembly on full-length NifU and truncated forms involving only the N-terminal domain or the central and C-terminal domains have been investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
122
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(129 citation statements)
references
References 56 publications
6
122
0
1
Order By: Relevance
“…Recent elegant studies showed that E. coli IscU or Azotobacter vinelandii NifU are capable of catalyzing Fe/S cluster transfer to target proteins without the need of further assistance of a chaperone (14,18). Even multiple rounds of cluster transfer were documented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent elegant studies showed that E. coli IscU or Azotobacter vinelandii NifU are capable of catalyzing Fe/S cluster transfer to target proteins without the need of further assistance of a chaperone (14,18). Even multiple rounds of cluster transfer were documented.…”
Section: Discussionmentioning
confidence: 99%
“…The protein pair Isu1p/Isu2p is essential for cell viability, and loss of function causes severe defects in cellular Fe/S protein maturation (11)(12)(13). Purified Isu1p and its bacterial homologs IscU/NifU bind mononuclear iron and Fe/S clusters that can be assembled by chemical or desulfurase-directed reconstitution (3,7,14). Three conserved cysteine residues of the Isu proteins are essential for the binding of iron or Fe/S clusters.…”
mentioning
confidence: 99%
“…The variants IscU D39A and Nfu-1 D39A were shown to be compromised in [Fe-S] cluster transfer to apo-aconitase and apo-dinitrogen reductase, respectively (64,65). These protein variants have been useful in dissecting the mechanism of [Fe-S] cluster biosynthesis and transfer (36, 66 -69).…”
Section: Variant Growth Atp Hydrolysismentioning
confidence: 99%
“…The central domain contains a stable redoxactive [2Fe-2S] cluster with an as-yet-unknown function (7). In vitro and in vivo experiments have established that labile [Fe-S] clusters can be assembled on both the N-terminal and C-terminal domains of NifU, and such cluster-loaded forms of NifU can be used for activation of the nitrogenase Fe-protein (8,9). Thus, NifU contains two different sites upon which labile [Fe-S] clusters can be assembled in vitro, but the functional relationship between these sites is not yet known.…”
mentioning
confidence: 99%